Retinal Function and Neural Conduction Along the Visual Pathways in Affected and Unaffected Carriers With Leber's Hereditary Optic Neuropathy - Ziccardi, Lucia; Sadun, Federico; De Negri, Anna Maria; Barboni, Piero; Savini, Giacomo; Borrelli, Enrico; Morgia, Chiara La; Carelli, Valerio; Parisi, Vincenzo (Investigative ophthalmology & visual science, 2013)
We assessed retinal ganglion cell (RGC) function, and established a correlation between the neural conduction along the visual pathways and the retinal involvement in Leber's hereditary optic neuropathy (LHON). A total of 39 individuals carrying a LHON mutation (mean age, 33.35 ± 8.4 years), LHON-unaffected (LU, 22 eyes) or LHON-affected (LA, 17 eyes), underwent visual acuity and visual field examinations. A total of 22 age-similar normal subjects (mean age, 38.2 ± 6.0 years) served as controls. In all subjects, simultaneous pattern electroretinograms (PERGs) and visual evoked potentials (VEPs) were recorded in response to 60-minute (60') and 15-minute (15') checkerboard stimuli. When compared to controls, LU eyes did not show any statistically significant difference in 60' and 15' VEP P100 implicit times (ITs), VEP N75-P100 amplitudes, and 60' PERG P50 ITs, whereas 15' PERG P50-N95 amplitudes were significantly (P < 0.01) reduced. When compared to control and LU eyes, LA eyes showed significant differences in PERG and VEP ITs, and amplitudes with both stimulations (60' and 15' checks). No significant correlations between PERG and VEP parameters were found in LU eyes, while in LA eyes, PERG P50 and VEP P100 ITs correlated significantly only when using 60' checks. The LHON-unaffected eyes showed a retinal dysfunction detected by abnormal PERG responses that was not associated with changes along the visual pathways assessed by normal VEP responses. In LA eyes, the impaired neural conduction recorded by VEPs in response to larger (60' VEP responses) and smaller (15' VEP responses) checks were associated and not associated, respectively, with the detected retinal dysfunction.